Matchmaker eaudiobook - Lyons, Kelly Starling (Miles Lewis, 2022)
From the award-winning author of the Jada Jones chapter books comes a spinoff series perfect for STEM fans! Valentine's Day is approaching, and Miles Lewis doesn't really like all the mush that comes with it. He is excited about the candy experiments they're doing in science class, though. And when his teacher asks for adult volunteers to help out, Miles and his friend Jada share that they're both planning on inviting their grandparents. That's when they realize that Miles's Nana and Jada's Pop Pop have a lot in common—could they be a perfect match?